2022
DOI: 10.1177/00110000211072199
|View full text |Cite
|
Sign up to set email alerts
|

Latinx Undergraduates’ Navigation in the Context of COVID-19 and Racial Injustice

Abstract: Six self-identified, first generation, Latinx, undergraduates from west coast public institutions were recruited via social media to participate in individual, semi-structured, qualitative interviews about their experiences with COVID-19 and racial injustice during the summer and fall of 2020. Interviews explored challenges and meaning-making around what had been happening in their lives and how they experienced and made sense of those events. Interpretative Phenomenological Analysis (IPA; Smith et al., 2009) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The findings of the study provide insight into the social, political, economic, and environmental stresses faced by the Latinx community, as well as how disparities and injustices have been magnified by the COVID-19 pandemic. The current study’s results are consistent with a recent qualitative study found that Latinx college students reported were worried about the future due to encountering social injustices during the pandemic ( Morgan and Zetzer, 2022 ). In our study, several participants reported experiencing barriers to accessing resources for themselves and their families, including the inability to obtain COVID-19 testing and health care, which led to additional burden and distress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the study provide insight into the social, political, economic, and environmental stresses faced by the Latinx community, as well as how disparities and injustices have been magnified by the COVID-19 pandemic. The current study’s results are consistent with a recent qualitative study found that Latinx college students reported were worried about the future due to encountering social injustices during the pandemic ( Morgan and Zetzer, 2022 ). In our study, several participants reported experiencing barriers to accessing resources for themselves and their families, including the inability to obtain COVID-19 testing and health care, which led to additional burden and distress.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, if some of the stressors affecting Latinx families during the pandemic are reduced (i.e., limited caregiving, barriers to health care, and increased targeted public health information in Spanish), then it is likely that the mental health of Latinx will also be improved ( Garcini et al, 2021 ). Based on the accounts of participants with regards to their exposure to social injustices, it is important for mental health providers to address the psychological impact that social injustices have had on them during the pandemic and to promote sources of strength and meaning ( Morgan and Zetzer, 2022 ).…”
Section: Study Implicationsmentioning
confidence: 99%
“…However, these individuals still find a way to make it through their day and become successful according to their own standards despite their toxic environment. Examples from the analyzed articles that conceptualized resilience in this manner include Parmenter et al (2021) and Morgan and Zetzer (2022). In their study on LGTBQ+ people of color, Parmenter et al (2021) identified resilience as “the ability to endure adverse impacts of stress and thrive in the face of adversity” (p. 630).…”
Section: Resultsmentioning
confidence: 99%
“…In their study on LGTBQ+ people of color, Parmenter et al (2021) identified resilience as “the ability to endure adverse impacts of stress and thrive in the face of adversity” (p. 630). In studying Latinx student experiences, Morgan and Zetzer (2022) cited Masten et al (2009) and defined resilience as, “the process and outcome of successfully adapting to challenging life experiences” (p. 417). Both empirical articles used qualitative research designs to examine resilience among these populations and relied on interviews to collect data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation